Health-related quality of life and treatment satisfaction in patients with gout: results from a cross-sectional study in a managed care setting - Khanna, Puja P (Patient Prefer Adherence, 2015)
BACKGROUND: Patient satisfaction with treatment directly impacts adherence to medication. OBJECTIVE: The objective was to assess and compare treatment satisfaction with the Treatment Satisfaction Questionnaire for Medication (TSQM), gout-specific health-related quality of life (HRQoL) with the Gout Impact Scale (GIS), and generic HRQoL with the SF-12v2(®) Health Survey (SF-12) in patients with gout in a real-world practice setting. METHODS: This cross-sectional mail survey included gout patients enrolled in a large commercial health plan in the US. Patients were ≥18 years with self-reported gout diagnosis, who filled ≥1 prescription for febuxostat during April 26, 2012 to July 26, 2012 and were not taking any other urate-lowering therapies. The survey included the TSQM version II (TSQM vII, score 0–100, higher scores indicate better satisfaction), GIS (score 0–100, higher scores indicate worse condition), and SF-12 (physical component summary and mental component summary). Patients were stratified by self-report of currently experiencing a gout attack or not to assess the discriminant ability of the questionnaires. RESULTS: A total of 257 patients were included in the analysis (mean age, 54.9 years; 87% male). Patients with current gout attack (n=29, 11%) had worse scores than those without gout attack on most instrument scales. Mean differences between current attack and no current attack for the TSQM domains were: −20.6, effectiveness; −10.6, side effects; −12.1, global satisfaction (all P<0.05); and −6.1, convenience (NS). For the GIS, mean differences were: 30.5, gout overall concern; 14.6, gout medication side effects; 22.7, unmet gout treatment needs; 11.5, gout concern during attack (all P<0.05); and 7.9, well-being during attack (NS). Mean difference in SF-12 was −6.6 for physical component summary (P<0.05) and −2.9 for mental component summary (NS). Correlations between several TSQM and GIS scales were moderate. CONCLUSION: The TSQM and GIS were complementary in evaluating the impact of gout flare on treatment satisfaction and HRQoL. Correlations between the two instruments supported the relationship between treatment satisfaction and HRQoL.